The weight of silence eaudiobook - Gudenkauf, Heather (Recorded Books Inc., 2010)
Masterfully written and beautifully told, Heather Gudenkauf's debut is a stunning novel of family devotion, honesty and regret that will linger long after the last page is turned. It happens quietly one August morning. As dawn's shimmering light drenches the humid Iowa air, two families awaken to find their little girls have gone missing in the night. Seven-year-old Calli Clark is sweet, gentle, a dreamer who suffers from selective mutism brought on by a tragedy that pulled her deep into silence as a toddler. Calli's mother, Antonia, tried to be the best mother she could within the confines of marriage to a mostly absent, often angry husband. Now, though she denies that her husband could be involved in the possible abductions, she fears her decision to stay in her marriage has cost her more than her daughter's voice. Petra Gregory is Calli's best friend, her soul mate and her voice. But neither Petra nor Calli has been heard from since their disappearance was discovered. Desperate to find his child, Martin Gregory is forced to confront a side of himself he did not know existed beneath his intellectual, professorial demeanor. Now these families are tied by the question of what happened to their children. And the answer is trapped in the silence of unspoken family secrets. "Deeply moving and exquisitely lyrical, this is a powerhouse of a debut novel."—Tess Gerritsen, New York Times bestselling author